2010
DOI: 10.1128/jvi.00202-10
|View full text |Cite
|
Sign up to set email alerts
|

A Human Herpesvirus MicroRNA Inhibits p21 Expression and Attenuates p21-Mediated Cell Cycle Arrest

Abstract: The oncogenic human gammaherpesvirus Kaposi's sarcoma-associated herpesvirus (KSHV) expresses 12 viral microRNAs (miRNAs) in latently infected cells. Here, we report that cellular mRNAs encoding the cellular cyclin-dependent kinase inhibitor p21, a key inducer of cell cycle arrest, are direct targets for KSHV miR-K1. Ectopically expressed KSHV miR-K1 specifically inhibited the expression of endogenous p21 in KSHV-negative cells and strongly attenuated the cell cycle arrest that normally occurs upon p53 activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 45 publications
1
128
0
Order By: Relevance
“…The post-transcriptional regulation of p21 by the embryonic stem cell-specific miRNAs, miR-290 cluster, was shown to promote the G1/S transition and rapid proliferation of embryonic stem cells (Wang et al, 2008). The Kaposi's sarcomaassociated herpes virus miR-K1 represses the expression of p21 and attenuates p21-mediated cell cycle arrest (Gottwein and Cullen, 2010). A number of miRNAs, such as miR-302a, miR-146a and miR-146b, which target p21 can rescue human mammary epithelial cells from Ras G12V -induced senescence by preventing the Ras G12V -induced upregulation of p21 (Borgdorff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The post-transcriptional regulation of p21 by the embryonic stem cell-specific miRNAs, miR-290 cluster, was shown to promote the G1/S transition and rapid proliferation of embryonic stem cells (Wang et al, 2008). The Kaposi's sarcomaassociated herpes virus miR-K1 represses the expression of p21 and attenuates p21-mediated cell cycle arrest (Gottwein and Cullen, 2010). A number of miRNAs, such as miR-302a, miR-146a and miR-146b, which target p21 can rescue human mammary epithelial cells from Ras G12V -induced senescence by preventing the Ras G12V -induced upregulation of p21 (Borgdorff et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We have recently demonstrated that nucleophosmin/B23 and hSSB1 may function as chaperones to protect p21 from degradation by the ubiquitin-proteasome pathway (Xiao et al, 2009;Xu et al, 2011). Interestingly, miRNAs such as the miR-17 family and human pathogenic gamma herpes virus Kaposi's sarcoma-associated herpes virus miR-K1 have also been reported to regulate p21 expression negatively at the post-transcriptional level via the p21 3 0 UTR (Gottwein and Cullen, 2010;Wang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The lentiviral miR-34a sponge, containing 6 imperfect matches for miR34a, was cloned in the vector pLCE as previously described (8,16) using the following oligonucleotides: Spng miR34 fw primer (5= CTAGCAACAACC AGGATAGACACTGCCAGTTTTGAACAACCAGGATAGACACTGCC AGTTTTGAACAACCAGGATAGACACTGCCATCTAGATTG 3= [targets are underlined; mismatch is in boldface]) and Spng miR34 rev primer (5= AATTCAAATCTAGATGGCAGTGTCTATCCTGGTTGTTCAAAA CTGGCAGTGTCTATCCTGGTTGTTCAAAACTGGCAGTGTCTATC CTGGTTGTTG 3=). The murine stem cell virus (MSCV)-based sponge was cloned by removing the DNA fragment containing the miR-34a binding sites from the pLCE-based sponge with NheI (then blunt)/EcoRI restriction enzymes and ligating it into the HpaI (then blunt)/EcoRIdigested pMSCV-Puro.…”
Section: Methodsmentioning
confidence: 99%
“…One major clue to the potential functions of the KSHV miRNAs is the identification of two of the KSHV miRNAs as viral analogs of the cellular miRNAs miR-155 and miR-142-3p (12,14,15). Several additional interactions and functions of the KSHV miRNAs have been identified (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35); however, the overall impact these miRNAs have on host gene expression and their phenotypic consequences remain largely unknown.…”
mentioning
confidence: 99%